Services quality of Islamic university - Irwan Misbach (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2018)
This study is to determine the level of student satisfaction with the service quality of islamic university. The study sample was 83 people based on accidental sampling, using Performance-Importance Analysis. The results of this study found that high religious students who received administrative and academic services were in the very satisfied category with a value of 98.3%. However, there is a service that must be a concern of the university, namely the ability of the university to respond or act quickly in solving problems faced by students. In addition, the quality of service that is prioritized is not very important for students, so the implementation seems ordinary because students are quite satisfied with the service. Services included in this category are representative service rooms, complete learning, attractive-looking staff, fast and appropriate services, and complicated procedures.